Mortality rate associated with carbon monoxide poisoning in Turkey: a national database study - Tugba Atmaca Temrel (Journal of the Pakistan Medical Association, 2020)
Objective: To investigate non-fire and unintentional deaths caused by carbon monoxide poisoning in the light of official national data, and to calculate the national mortality rate associated with carbon monoxide poisoning in Turkey. Methods: The retrospective cross-sectional study was conducted in Ankara, Turkey, from January to March 2019, and comprised data of deaths registered with the Turkish Statistical Institutebetween January 1, 2013, and December 31, 2017. Data was analysed using SPSS 21. Results: Of the 1896 deaths, 1310(69.1%) were males, and the highest number of deaths 622(33%) was recorded in 2014. Deaths were most common in the 18-64 years age group 1071(56.6%). Overall, there were 1841(97.1%) Turkish citizens and 55(92.9%) foreign nationals. Manisa had the highest number of deaths 266(14%) at a mortality rate of 3.84 per 100,000 population. Conclusion: The factual situation of death associated with carbon monoxide in Turkey will lead to steps to reduce the risk. Key Words: Carbon monoxide poisoning, Mortality rate, Unintentional poisoning. Continuous...